Exploring quality in a university : a critical systems approach : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Educational Studies at Massey University, Palmerston North, New Zealand - Houston, Donald James (Massey University, 2007)
Since the 1990s quality management has been translocated from industry into higher education. However, there is little evidence that improvement in the core functions of universities has resulted. This study adopts a critical systems approach that is grounded in a critique of prevailing models of quality management to explore quality in a university. It examines the potential of Critical Systems Thinking enacted through Total Systems Intervention (TSI) to promote improvement. A case is made for local intervention towards improvement. The thesis is structured around the three modes of TSI, namely Critical Review, Problem Solving and Critical Reflection. A Critical Review of Quality Management suggests that the opposition of academics to quality initiatives in general, and to Quality Management in particular, is rooted in its language and underlying image of organization. This proposition is explored through an analysis of key Quality Management definitions and concepts in relation to the university. The importance of language, metaphors and images of organization are explored. The fitness for purpose of industrial models of quality for universities is challenged. TSI is employed in its Problem Solving mode to describe the quality problem for an academic unit within a university in New Zealand initially from the perspective of its staff and students. For them, the quality problem mainly related to better promoting learning. Analysis and reflection on the problem and context drawing on systems methodologies shaped interventions for improvement. Critical Reflection on a cycle of participative creativity, choice and implementation identified cultural, structural and environmental factors that present threats not only to quality improvement but also to the viability of the unit. The main findings and conclusions question the appropriateness of current models of QM in the university. The thesis demonstrates key systemic problems in higher education; provides a rationale for systemic interventions; identifies pressures that make resistance to systems thinking almost inevitable; and illustrates that TSI is more appropriately used by external researchers than insider researchers. Nevertheless, critical systems approaches, in particular boundary critique, help to structure the problem of improving quality in locally meaningful ways. The challenges of using systems ideas and systems methodologies in the university context, however, are substantial.
Keywords: University; Administration; Total quality management; Higher education; Fields of Research::330000 Education::330100 Education Studies::330104 Educational policy, administration and management